2015
DOI: 10.1016/j.jiph.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of cytokines in Quantiferon supernatants for the diagnosis of latent TB infection in a tribal population of Melghat, India

Abstract: The tuberculin skin test (TST) and interferon-gamma release assays (IGRA), namely, the QuantiFERON-TB Gold test (QFT), remain the standard immunological diagnostic tools for latent tuberculosis (TB) infection (LTBI). However, the sub-optimal detection rates of both of these tests are major impediments in recognizing the population at risk. This study was aimed at evaluating additional cytokines besides interferon-gamma (IFN-γ) as biomarkers for improving LTBI diagnosis in the tribal population of Melghat, Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Whereas others confirmed the capability of IL-6 to detect M. tuberculosis in contacts of tuberculosis patients [28], own previous studies indicated a minor capacity of IL-6 in a tuberculosis low-endemic region [22]. IP-10, a potential biomarker described to improve sensitivity of IGRAs especially in children [16,29] and in HIV co-infection [30,31] detected low proportions of particularly HIV co-infected children.…”
Section: Discussionmentioning
confidence: 95%
“…Whereas others confirmed the capability of IL-6 to detect M. tuberculosis in contacts of tuberculosis patients [28], own previous studies indicated a minor capacity of IL-6 in a tuberculosis low-endemic region [22]. IP-10, a potential biomarker described to improve sensitivity of IGRAs especially in children [16,29] and in HIV co-infection [30,31] detected low proportions of particularly HIV co-infected children.…”
Section: Discussionmentioning
confidence: 95%
“…The serum cytokines levels of severe HFMD, interleukin-1β (IL-1β), IL-2, IL-6, IL-8, IL-10, interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α) were determined by using the IMMULITE-1000 Immunoassay System (Siemens Healthcare Global), an automated microbead-based analyzer that makes use of chemiluminescent technology for analyte detection, which was performed according to the manufacturer’s instructions [20]. Serum cytokines levels of 50 mild EV-A71, and 50 CV-A16 HFMD cases, and 100 healthy individuals were also measured.…”
Section: Methodsmentioning
confidence: 99%
“…However, after stimulation, we observed that the secretion of IFN-γ and TNF-α by NK cells was remarkably decreased in ATB patients. In general, NK cells are not only the key effectors in the innate immune response to various infections (Bapat et al, 2015 ), but are also the effective regulators in innate and adaptive immune responses (Deng et al, 2014 ). In accordance with previous studies (Kim et al, 2015 ; Pan et al, 2015 ), our results indicate that the impaired cytokine production by NK cells may be an important factor in TB development.…”
Section: Discussionmentioning
confidence: 99%